Museums and heritage tourism theory, practice and people - White, Chris 1966- (Abingdon, Oxon New York, NY Routledge, 2023)
"White examines the symbiotic relationship between museums, heritage attractions, and tourism, using a range of international case studies. Divided into three clear sections, White first outlines a theoretical framework for understanding the role of museums in heritage tourism, before addressing practical challenges of interpretation, design, and pandemic response. Finally, he traces the development of museum and heritage attraction design through the key figures of John Ruskin, James Gardner and Alex McCuaig. Each chapter incorporates a key case study, with an international scope including examples from Hong Kong, the UK, Taiwan, Qatar, Dubai, and Kuwait. An essential introduction for undergraduate and graduate students taking courses in museum studies, heritage studies, and tourism management"--
History vs heritage -- Heritage tourism -- Museums as tourism attractions -- Issues in interpretation -- Museum design management -- Museums in an age of pandemics -- John Euskin : learning to look -- James Gardner : interacting to learn -- Alex McCuaig : experiencing to inspire.
Includes bibliographical references and index.
Keywords: Heritage tourism; Museums -- Social aspects